Evaluating the Alimentary and Respiratory Tracts in Health and disease (EARTH) research programme: a protocol for prospective, longitudinal, controlled, observational studies in children with chronic disease at an Australian tertiary paediatric hospital. Issue 4 (14th April 2020) - Coffey, Michael J; McKay, Isabelle R; Doumit, Michael; Chuang, Sandra; Adams, Susan; Stelzer-Braid, Sacha; Waters, Shafagh A; Kasparian, Nadine A; Thomas, Torsten; Jaffe, Adam; Katz, Tamarah; Ooi, Chee Y
Abstract : Introduction: Chronic gastrointestinal and respiratory conditions of childhood can have long-lasting physical, psychosocial and economic effects on children and their families. Alterations in diet and intestinal and respiratory microbiomes may have important implications for physical and psychosocial health. Diet influences the intestinal microbiome and should be considered when exploring disease-specific alterations. The concepts of gut-brain and gut-lung axes provide novel perspectives for examining chronic childhood disease(s). We established the 'E valuating the A limentary and R espiratory T racts in H ealth and disease' (EARTH) research programme to provide a structured, holistic evaluation of children with chronic gastrointestinal and/or respiratory conditions. Methods and analysis: The EARTH programme provides a framework for a series of prospective, longitudinal, controlled, observational studies (comprised of individual substudies), conducted at an Australian tertiary paediatric hospital (the methodology is applicable to other settings). Children with a chronic gastrointestinal and/or respiratory condition will be compared with age and gender matched healthy controls (HC) across a 12-month period. The following will be collected at baseline, 6 and 12 months: (i) stool, (ii) oropharyngeal swab/sputum, (iii) semi-quantitative food frequency questionnaire, (iv) details of disease symptomatology, (v) health-related quality of life and (vi) psychosocial factors. Data on the intestinal and respiratory microbiomes and diet will be compared between children with a condition and HC. Correlations between dietary intake (energy, macro-nutrients and micro-nutrients), intestinal and respiratory microbiomes within each group will be explored. Data on disease symptomatology, quality of life and psychosocial factors will be compared between condition and HC cohorts. Results will be hypothesis-generating and direct future focussed studies. There is future potential for direct translation into clinical care, as diet is a highly modifiable factor. Ethics and dissemination: Ethics approval: Sydney Children's Hospitals Network Human Research Ethics Committee (HREC/18/SCHN/26). Results will be presented at international conferences and published in peer-reviewed journals. Trial registration number: NCT04071314